SPICE Modeling of Memcomputing Logic Gates - Pershin, Y. V. (Společnost pro radioelektronické inženýrství, 2023)
Memcomputing logic gates generalize the traditional Boolean logic gates for operation in the reverse direction. According to the literature, this functionality enables efficient solution of computationally intensive problems, including factorization and NP-complete problems. To approach the deployment of memcomputing gates in hardware, this paper introduces SPICE models of memcomputing logic gates following their original definition. Using these models, we demonstrate the behavior of single gates as well as small self-organizing circuits. We have also corrected some inconsistencies in the prior literature. Notably, the correct schematics of the dynamic correction module is reported here for the first time. Our work makes memcomputing more accessible to those interested in this emerging computing technology.
Keywords: Memristors; SPICE; nonlinear dynamical systems; computing technology